2005
DOI: 10.1002/hfm.20033
|View full text |Cite
|
Sign up to set email alerts
|

The integration of work process knowledge into human resources development

Abstract: In this contribution the relationship between work process knowledge and human resources development is discussed. The concept of work process knowledge is described as it evolved as an outcome of a research network involving research institutions from 10 European countries (N. C. Boreham, R. Samurçay, & M. Fischer, 2002). Historical origins of the concept are mentioned and different dimensions of work process knowledge are depicted as a topic of ongoing research. How work process knowledge is considered withi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…This study builds on the work of previous researchers in this field (Boreham, 2002a, b; Mariani, 2002; Boreham, 2004a, b; Fischer and Boreham, 2004; Clases and Wehner, 2004; Fischer, 2005; Fischer et al , 2004). Like these previous authors, this study found that employees with well‐developed WPK understand the organisation they work in at the strategic level, how all the departments fit and work together, their own importance in the overall scheme of things and the goals of the organisation.…”
Section: How the Organisations Developed Wpkmentioning
confidence: 69%
See 1 more Smart Citation
“…This study builds on the work of previous researchers in this field (Boreham, 2002a, b; Mariani, 2002; Boreham, 2004a, b; Fischer and Boreham, 2004; Clases and Wehner, 2004; Fischer, 2005; Fischer et al , 2004). Like these previous authors, this study found that employees with well‐developed WPK understand the organisation they work in at the strategic level, how all the departments fit and work together, their own importance in the overall scheme of things and the goals of the organisation.…”
Section: How the Organisations Developed Wpkmentioning
confidence: 69%
“…WPK is held not only within the individual but is also socially and culturally based, with knowledge and information shared through common language and artefacts within the workplace (Boreham, 2004b; Fischer et al , 2004; Fischer, 2005; Lammont and Boreham, 2002; Norros and Nuutinen, 2002; Waibel‐Fischer et al , 2004). Organisational structure, formal and informal communication structures, organisational climate, division of labour and management approaches have been shown to play a major part in the development of WPK by workers (Heinz et al , 2004; Waibel‐Fischer et al , 2004).…”
Section: Wpk As a Conceptual Frameworkmentioning
confidence: 99%